Возможности оптимизации бизнес-процессов на промышленных предприятиях - Лысенко (Звёздочкина), Елена Анатольевна (My University, 2014)
В работе рассмотрена необходимость оптимизации бизнес-процессов на промышленных предприятиях. Обобщена классификация бизнес-процессов на предприятиях машиностроения. Представлена модель сети основных и поддерживающих бизнес-процессов предприятия ПАО «Запорожтрансформатор» с целью их дальнейшей оптимизации. In this paper, a need of optimization of business processes at the industrial enterprises is considered. The classification of business processes at the mechanical engineering enterprises is generalized. The model of a network of the main and supporting business processes of the enterprise Public Joint-stock Company "Zaporozhtransformator" for their further optimization purposes is presented.
Keywords: бизнес-процесс; оптимизация; предприятие; классификация; макропроцесс; модель; business process; optimization; enterprise; classification; macroprocess; model; кафедра економіки праці та менеджменту